The use of technology and its relation to the productive chain of the quinua in the farmers of the Cabana locality of the Region of Puno, 2016 - Avalos Huamani, Carmen Vicente (2018)
The present investigation has as objective to know the existent relation between the use of the technology and the productive chain of the quinoa of the agriculturists in the locality of Cabana in the region of Puno, 2016. The investigation is Basic, with descriptive design. The research was developed in the geographic area of the town of Cabana, Province of San Román; Department of Puno and Puno region, in the 2016 period. The population was composed by the inhabitants of the area dedicated to the production of quinoa. The analyzed population is made up of 2,625 Quinoa-producing families from the District of Cabana / Puno. The sample is random and significant with a size of 262 families producing Quinoa from the District of Cabana / Puno. We worked with a structured questionnaire. The results of the research show that the quinoa producing families have adequate knowledge about the use of technology, as well as the productive chain. It is concluded that there is a significant relationship between the use of technology with the production chain of quinoa production in the farmers of the Cabana District, San Román Province; Department and Region Puno.